Bioinspired Integration of Naturally Occurring Molecules towards Universal and Smart Antibacterial Coatings. (23rd October 2021) - Yang, Lei; Wang, Changping; Li, Lin; Zhu, Fang; Ren, Xiancheng; Huang, Quan; Cheng, Yiyun; Li, Yiwen
Abstract: Surface‐independent smart antibacterial coatings with on‐demand antibiotics release profiles have attracted increasing attention in medical instruments, antibiotics delivery platforms, and implanted devices. Although several approaches have been well documented, the facile preparation of antibacterial coatings onto universal substrates with high antibiotics loading efficiencies, tunable drug release profiles, and excellent antibacterial performances is still met with many challenges, especially related to the redundant coating material synthesis and selective substrate fabrication process. To resolve this issue, the authors report a facile and robust fabrication method towards smart antibacterial coating surfaces on various substrates via a one‐pot integration of two types of naturally occurring building blocks, aminoglycosides and protocatechualdehyde in the presence of plant enzyme horseradish peroxidase. The simultaneous dynamic imine bonds formation and enzymatic polymerization within the system during the one‐pot reaction enable the facile fabrication of diverse surface‐independent smart antibacterial coatings, which can demonstrate several promising features including high drug loading and dynamic (i.e., pH‐responsive) properties, tunable and on‐demand antibiotics release behaviors, and efficient antibacterial activities both in vitro and in vivo. This work may offer new opportunities towards the robust and universal antibacterial coating materials by the bioinspired integration of all natural building blocks. Abstract : A facile and robust preparation strategy towards universal and smart antibacterial coatings is established via a one‐pot integration of two types of naturally occurring building blocks, aminoglycosides and protocatechualdehyde in the presence of plant enzyme horseradish peroxidase. Several promising features including dynamic (i.e., pH‐responsive) properties, tunable antibiotics release behaviors, and efficient antibacterial activities are demonstrated.